2019
DOI: 10.1021/acsomega.9b02845
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profile of the Digestive Enzymes of Manis javanica Reveals Its Adaptation to Diet Specialization

Abstract: The expression of animal digestive enzymes reflects important dietary adaptations. The pangolin, also known as scaly anteater, is a specialized myrmecophage that consumes mainly ants and termites, but its digestive enzymes have not been fully investigated. Therefore, in this study, we used shotgun proteomic analysis to examine the protein components of the saliva and intestinal juice of a Sunda pangolin (Manis javanica) that died shortly after being rescued. The intestinal juice contained greater variety of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…In line with the improved growth performance in Thy and ThQ mixture group, the expression levels of digestive enzymes (pepsinogen, chymotrypsinogen, α-amylase and lipase) encoding genes were also provoked. Digestive enzymes synthesis can be modified by genes, hormones and nutritional aids [ 67 ] and their higher expression levels reflect the important function of specific dietary feed additives or even their adaptations by animals [ 69 , 70 ]. Herein, the upregulated expression of pepsinogen, chymotrypsinogen, α-amylase and lipase genes after feeding on Thy and ThQ mixture indicated their promising roles in enhancing the formation of such digestive enzymes, which in turn have a positive influence on the digestive process and feed utilization.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the improved growth performance in Thy and ThQ mixture group, the expression levels of digestive enzymes (pepsinogen, chymotrypsinogen, α-amylase and lipase) encoding genes were also provoked. Digestive enzymes synthesis can be modified by genes, hormones and nutritional aids [ 67 ] and their higher expression levels reflect the important function of specific dietary feed additives or even their adaptations by animals [ 69 , 70 ]. Herein, the upregulated expression of pepsinogen, chymotrypsinogen, α-amylase and lipase genes after feeding on Thy and ThQ mixture indicated their promising roles in enhancing the formation of such digestive enzymes, which in turn have a positive influence on the digestive process and feed utilization.…”
Section: Discussionmentioning
confidence: 99%
“…There have been some studies investigating the anatomy and morphology of limb muscles, masticatory muscles, digestive organs and enzymes, and reproductive organs of primarily the Asian pangolin species (Akmal et al, 2019;Kawashima et al, 2015;Zhang et al, 2019). The unique tongue and its associated structures seem to be the most widely studied aspect of the pangolin (Abayomi et al, 2009;Doran & Allbrook, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…The brush border staining of CD26/DPP4 has been documented in the small and/or large intestine of rats (Dinjens et al 1989a;McGaughan et al 1990), mice (Mentzel et al 1996), pigs (Poulsen et al 1993), and humans (Hansen et al 1999). CD26/ DPP4 exists in intestinal juice obtained from the Sunda pangolin, insect-eating mammals (Zhang et al 2019), although it is unknown whether the enzyme originates from the intestine or pancreas. An in vitro study using human intestinal cell lines reported that intestinal epithelial cells secreted exosome-like vesicles containing CD26/DPP4 (van Niel et al 2001).…”
Section: Intestine and Lungmentioning
confidence: 99%